Highly Efficient Reduction of 4‐Nitrophenol by Cu Nanoparticle Decorated Graphdiyne. Issue 47 (16th December 2021) - Xie, Shuanglei; Xu, Ze; Yu, Cong; Yu, Xianglin; Zhang, Zihe; Li, Junbo
Abstract: Catalytic reduction of 4‐nitrophenol (4‐NP) to 4‐aminophenol (4‐AP) over high‐performance and stable metal nanoparticle catalyst is highly desirable. This study experimentally demonstrated that graphdiyne (GDY), an all‐carbon two‐dimensional material composed of two hybrid carbon atoms (sp and sp 2 ), can uniformly disperse copper nanoparticles through simple microwave reduction and has excellent 4‐NP reduction ability. Cu/GDY shows an extraordinary reaction rate constant of 0.9984 min −1, Moreover, the catalytic activity is maintained almost intact within five cycles. These encouraging results demonstrated that the unique pores and electronic structure of GDY enhance the stability of anchored metal nanoparticles and have great potential to degrade 4‐NP as a promising support for copper nanoparticles. Abstract : The copper nanoparticle composite catalysts prepared with graphdiyne as the substrate through its special acetylene bond structure shows excellent 4‐nitrophenol (4‐NP) reduction performance, with the reaction rate constant was 0.9984 min −1 . More importantly, the conversion efficiency did not reveal significant decline even after 5 five cycles. This provides a strategy to solve the instability of metal nanoparticles in the catalytic process.